Pengaruh Edukasi terhadap Kepatuhan Siswi Usia Remaja dalam Penggunaan Tablet Tambah Darah - Debi Rianti; Suryani Suryani; Anna Choirunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of education on the adherence of adolescent girls to iron supplementation tablets (IST). Anemia in adolescent girls is a significant health problem, influenced by iron loss during menstruation and increased iron requirements during growth. Low adherence to IST consumption is caused by various factors, including unpleasant side effects after consuming IST, the perception of being healthy and not needing medication, and a lack of knowledge about the dangers of iron deficiency anemia in adolescence. The method used is a narrative review, with research journal sources related to the adherence of adolescent girls in consuming IST. These research journals were obtained from Google Scholar and selected those published in the last five years (2019-2023). The review results indicate the importance of education in increasing adherence to IST consumption. Audiovisual methods, such as videos and YouTube, have proven effective. Additionally, support from health workers and pharmacists is crucial in increasing the adherence of adolescent girls to IST consumption. It is concluded that innovative education and good support are essential in increasing the adherence of adolescent girls to IST consumption.